THE DEVELOPMENT OF A FRAMEWyORK FOR RESEARCH METHODOLOGY IN ISLAMIC AND MUSLIM STUDIES FOR APPLICATION IN HIGHER EDUCATION INSTITUTIONS OFFERING ISLAMIC STUDIES PROGRAMS IN THAILAND - Katih, Ismaie (Journal of MCU Nakhondhat, 2025)
This study aims to develop a framework for research methodology in Islamic and Muslim studies that can be effectively applied within the context of higher education institutions offering programs in Islamic studies in Thailand. Emphasis is placed on integrating Islamic principles with contemporary methodological approaches to produce knowledge that is accurate, ethical, and responsive to the needs of contemporary Muslim societies. The study employs a qualitative research design, collecting data from two primary sources: academic literature and structured interviews with 22 experts from eight institutions. The data from both sources were analyzed in parallel by comparing insights from the literature with expert opinions, then synthesizing them within an Islamic epistemological framework alongside modern research paradigms. The analysis emphasizes systematicity, conceptual accuracy, and contextual relevance to the socio-religious realities of contemporary Thai Muslim society, both in theory and practice, to promote localized applicability. Findings from the document analysis and expert consultations led to the formulation of a seven-component integrated framework: 1) Selecting research topics that address contemporary issues within Muslim communities, 2) Articulating research objectives and questions grounded in Islamic principles, 3) Choosing research paradigms that integrate revelation (wahy) with modern approaches, 4) Applying theoretical frameworks based on the Qur’an and Sunnah, 5) Employing data collection and citation methods aligned with Islamic scholarly ethics, 6) Analyzing data based on Islamic values such as justice (Al-‘Adl) and evidence (Al-Bayyinah), and 7) Preparing bibliographies and appendices systematically. This research contributes to curriculum development, instructional practices, and the cultivation of researchers capable of integrating faith with effective responses to contemporary societal challenges.